(untitled) (Annals of Bangladesh Agriculture, 2026)
Pest and weed infestations pose significant challenges to crop production in Bangladesh, where most farmers rely on manually operated sprayers that are labor-intensive, inefficient, and ergonomically taxing. To address these issues, a power-operated sprayer was designed, fabricated, and evaluated in this study. The developed sprayer integrates a gasoline engine with a mobile frame equipped with multiple nozzles, enabling high-pressure pesticide application with reduced human effort. Performance evaluation was conducted under both laboratory and field conditions. Key parameters such as spraying angle, discharge uniformity, swath width, overlap, field capacity, and operational cost were analyzed. Laboratory results demonstrated uniform nozzle discharge with low coefficient of variation (1.92%), consistent spray coverage, and optimal spraying angles across variable boom heights. Field trials on eggplant crops revealed a theoretical field capacity of 0.89 ha/h, an actual field capacity of 0.72 ha/h, and a field efficiency of 80.86%. The total operational cost was estimated at Tk. 295.07 per hectare with a break-even area of 52.54 ha. The power sprayer significantly reduces operator fatigue and enhances application efficiency, making it a promising solution for sustainable pesticide application in Bangladesh and similar agro-ecological contexts. Ann. Bangladesh Agric. 29(2): 45-66